The repeal of helmet use laws and increased motorcyclist mortality in the United States, 1975-1978. - Watson, G S (1980)
Monthly mortality figures for motorcyclists for each state in the United States were obtained for the period January 1975 through December 1978. Twenty-four states revealed or weakened their helmet use laws at various dates within this period. Two of these states subsequently reintroduced a strengthened law. This paper measures the effects of these law changes on motorcyclist mortality. The states that repealed or weakened their helmet laws were matched with one or more states from the same geographic region that either did not have helmet use laws or did not change such existing laws in this four-year period. The effect of weakening the law in each state was then estimated in three steps: 1) the mortality data from each state for the period prior to repeal were regressed on smoothed data from the matched states; 2) these equations were used to predict the numbers of motorcyclist deaths that would have been expected in each state in the period following the repeal or weakening of the law if the laws had not been changed; 3) these numbers of expected deaths were then compared with the actual numbers of deaths that occurred. Of the 26 law changes, it was found that 23 resulted in a greater number of actual deaths in the period following the repeal or weakening of the law than were predicted to occur if the law had not been changed. It is estimated that the repeals or weakening of motorcyclist helmet use laws were typically followed by almost 40 per cent increases in the numbers of fatally injured motorcyclists.